Les conseils de continuum : vers un collectif situé au service de l'orientation - Gabriela Valente; Sabrina Labbé; Varvara Ciobanu-Gout; Naïma Marengo; Vanessa Vidaller; Marie Cassagnes
The continuum councils established within the framework of the ACORDA project serve as departmental forums dedicated to discussions and local initiatives. The project was initially conceptualized with the goal of uniting the various stakeholders in the guidance process. It's aim was to foster collaboration and provide support, ultimately facilitating a more successful transition for students into higher education. This article delves into the role of continuum councils, drawing insights from data gathered during two council sessions within the same department. The findings underscore that these councils serve as a valuable platform for cultivating collective engagement among diverse participants, facilitating the exchange of experiential knowledge, and fostering a shared understanding of guidance principles.